INFORMATION SECURITY IN WIRELESS SENSOR NETWORKS (Modern information system and technologies, 2018)
In this work, the analysis of threats to the information resources that are processed in systems using wireless sensor networks. Systematized the possible types of attacks on sensor networks and the proposed security mechanisms in sensor networks that can significantly minimize threats to information security of wireless sensor networks. Keywords: wireless technology, data transmission, sensor networks, information security.